Chinese Preschool Children’s Socioemotional Development: The Effects of Maternal and Paternal Psychological Control - Xing, Shufen; Gao, Xin; Song, Xinxin; Archer, Marc; Zhao, Demao; Zhang, Mengting; Ding, Bilei; Liu, Xia (Frontiers in Psychology, 2017)
The present study examined the relative prediction and joint effects of maternal and paternal psychological control on children’s socioemotional development. A total of 325 preschool children between the ages of 34 and 57 months (M = 4 years 2 months) and their parents participated in the study. Fathers and mothers respectively reported their levels of psychological control and mothers evaluated the socioemotional development of children using two indicators (i.e. behavioral problems and prosocial behaviors). The results indicated that the relative predictive effects of maternal and paternal psychological control on children’s socioemotional development differed. Specifically, maternal psychological control was a significant predictor of children’s behavioral problems and prosocial behaviors, whereas the levels of paternal psychological control were unrelated to children’s socioemotional development. With regard to the combined effects of maternal and paternal psychological control, the results of ANOVAs and simple slope analysis both indicated that children would be at risk of behavioral problems as long as they had one highly psychologically controlling parent. High levels of paternal psychological control were associated with increased behavioral problems of children only when maternal psychological control was low. However, the association between maternal psychological control and children’s behavioral behaviors was significant, despite paternal psychological control.